Learning Innovations for Addressing Emerging Challenges of Adult Education Instruction in Nigeria During Covid-19 Pandemic - Inusa , Diana; Umar , M. Abubakar (Kashere Journal of Education, 2022)
Education of citizens is a right enshrined in diverse documents of the international organization evidenced by declarations and treaties. This right was truncated by COVID-19 pandemic when schools were closed in almost every country at diverse times. Apart from live learning centres being shutdown, several other challenges financial constraints, unemployment, poor learning and academic achievement emanated from the pandemic which jeopardize the educationally vulnerable adult learners. Hence, the emergence of asynchronous strategies of transmitting knowledge to learners. These strategies include distance, online, zoom and mass media learning methods. These new ways of learning have the tendencies of absorbing the effect of the pandemic and curtailing the spread of the virus as well as improving the standard of learning environment and societal development. The study recommends that; infrastructure of the online or distance education system needs to be strengthened; access to every adult learner should be established; in-service training should be provided to instructors in order to improve instructors’ distance or online teaching competencies.